Life History Evolution and Genome Size in Subtribe Oncidiinae (Orchidaceae) - CHASE, MARK W. (Ann Bot, 2005)
• Background and Aims Within Oncidiinae, there are several groups of species that are effectively annuals, and we wished to see if these species had smaller genome sizes than average for the subtribe. • Methods Fifty-four genome size estimates (50 of which are new) for species in subtribe Oncidiinae (Orchidaceae) were examined for the first time in a phylogenetic context to evaluate hypotheses concerning genome sizes and life history traits. • Results and Conclusions Within the limits of still relatively sparse sampling, the species that are effectively annuals do appear to have smaller genome sizes than average. However, the genome sizes of their immediate sister group are also small, indicating that changes in genome size preceded the change in life history traits. Genome sizes and chromosome numbers also do not correlate; some slowly growing species have lower chromosome numbers but large genomes and vice versa. Based on a survey of the literature on orchids, it is also clear that epiphytic species have smaller genome sizes than do terrestrial species, which could be an effect of different water relations or the fact that most terrestrial orchids are geophytic or have distinct growth and dormancy phases.